Young Children's Memories for Social Actions: Influences of Age, Theory of Mind, and Motor Complexity. Issue 1 (24th July 2020) - Gerson, Sarah A.; Meyer, Marlene
Abstract : Children learn actions performed by a social partner better when they misremember these actions as their own. Identifying the factors that alter the propensity to make appropriation errors is critical for optimizing social learning. In two experiments ( N = 110), we investigate the developmental trajectory of appropriation errors and examine social‐cognitive and motor‐related factors in 3‐ to 8‐year‐olds. Children with better theory of mind (ToM) skills made fewer appropriation errors for motorically complex actions. Appropriation errors did not differ as a function of ToM if children could perform the corresponding actions. A second experiment replicated this effect and found no influence of collaborative context on appropriation errors. This research sheds light on the complex relations among development, social‐cognition, and motor‐related factors.